Penentuan Faktor Kunci Untuk Pengembangan Pengelolaan TPST-Bantargebang Berkelanjutan: Pendekatan MICMAC - Tatan Sukwika (Diponegoro University, 2021)
The development of the area in the TPST-Bantargebang moved by conditions of decreasing capacity in the zone. The resulting negative externalities have had an impact on social and environmental conflicts for the surrounding community. The success of developing an area is determined by the existence and effectiveness of the roles of each stakeholder involved. Therefore, this study is important to do, especially for the development of sustainable management of TPST-Bantargebang. The objective of this research focused on finding the key factors driving the development of TPST-Bantargebang management. The method used is the MICMAC analysis approach. Retrieval of data through interviews key informants (experts) that determined based on the results of the snowball method. The results of the analysis show that there are important key factors, namely the development of human resource capacity and environmental carrying capacity. It recommended that the management of the TPST-Bantargebang establish a development scenario for the development of the TPST-Bantargebang based on these two key factors are in the social and environmental dimensions.